Hubungan Tingkat Pengetahuan Penggunaan Obat dengan Kepatuhan Minum Obat pada Pasien Hipertensi di Puskesmas - Niken Dyahariesti; Richa Yuswantina; Eflina Devita Sablon; Yola Nasinta (Fakultas Farmasi Universitas Pancasila, 2023)
Hypertension is a silent killer disease because the symptoms are often without complaints and the treatment requires a long period of time, so the outcomes are greatly affected by patient compliance. Hypertension is one of the main factors causing heart problems, kidney failure and cerebrovascular disease. Compliance with taking medication in patients with hypertension is very important because it can control blood pressure to prevent complications. This study was conducted to determine the relationship between knowledge and drug compliance in hypertensive patients. The measurement of knowledge was done using the Hypertension Knowledge-Level Scale (HK-LS) questionnaire and the measurement of compliance using the Morisky Medication Adherence Scale (MMAS-8) questionnaire. The samples used were patients at Pasir Panjang community health center and Buntok community health center with a total sample of 95 people. The results obtained, the level of good knowledge was 39%, 33% sufficient knowledge and 28% less knowledge. Meanwhile, the high level of compliance is 41% and the level of compliance is 31% and the level of knowledge is at 28%. Data analysis using the chi-square test showed p-values of <0.05 which means that there was a relationship between the level of knowledge and drug compliance in hypertensive patients.